Problems and challenges in Human Resource Management: A case of a large organization in Pakistan - Ali Irshad; Toor Shamas-Ur-Rehman (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2008)
This paper critically analyzes the work culture for a mainstream financial organization operating within Pakistan, while drawing a specific example to elucidate certain dilemmas that impede the potential growth for the financial sector and its constituent workforce, besides hampering the performance of the organizations. The case study is related to an organization in financial sector which conducts a Management Trainee Program with the purpose to select, train and develop a high-potential pool of talent into future leaders and fore-runners of the organization. This paper critically analyzes several inherent problems that face the successful implementation of the trainee program under the frameworks of various theories of organizational management. To solve these problems, this article presents a detailed diagnosis of the management shortcomings to improve the firm.s corporate culture, work ethics and employee handling strategy and mechanism. Recommendations are also made to minimize the problems and maximize the success of the Management Trainee Program in the case study organization.
Keywords: 330; Human resource management; management trainee program; problems; challenges; motivation